A Methodology for Quality Management of Teacher Performance in a University Teach-ing Department - Polo Vega, Juan Carlos (Rastros Rostros, 2013)
This article describes the main elements of a methodology aimed at improving quality management of teacher performance in a university department, as well as some results of its practical application. Its design was born from the quality management principles which form the basis of the iso 9000 standards, adapted to the Cuban university context. It was also shaped by the need for improvement in teacher performance management that was detected in many faculties at Universidad de La Habana. A process-based approach was used for planning, control, evaluation and teacher performance improvement, employing tools such as process maps, student opinion surveys and guides for self-evaluation of teacher performance –all of which were designed for this purpose. Results of applying this methodology included an improvement in the quality of individual and department-wide work plans, greater clarity among the staff regarding the performance expected of them, more considered self-evaluations, fairer teacher evaluations and greater staff participation in the evaluation process, which has optimized department management in relation to the quality of academic performance